LA INCONCEBIBILIDAD DE LA POBREZA EN LA SOCIEDAD LIBRE. EL ARGUMENTO JURÍDICO. - , Luca Moratal Roméu (REVISTA PROCESOS DE MERCADO, 2024)
Poverty, an open wound on humanity, is also a pending issue for libertarian political theory, the current of thought that advocates minimization of coercion, and thereby maximization of freedom, as an ideal of social organization. While libertarians have prolifically argued that a free society would be much more prosperous in all its strata, they have never sought to demonstrate so ambitious a proposition that such a society would become incompatible with the very phenomenon of poverty. This essay provides demonstration thereof by means of a legal-philosophical argument built upon the legal treatment that so-called famine theft would presumably receive in the non-statist legal community. Based on the primacy of human life and dignity over any other legal value, famine theft would constitute an exception to the inviolability of private property. Echoing the historical development of maintenance obligations arising from a family relationship, the evolutionary nature of decentralized law would gradually widen the range of material needs suitable to qualify as determinants of poverty, the presence of which would legitimize the resort to this exception. Likewise, it would spontaneously result in the voluntary articulation of social assistance networks, the contribution to which would be judicially recognized as a counter-exception to the admissibility of famine theft and similar behaviors—thus affording full legal protection of property.